New evidence that biallelic loss of function in EEF1B2 gene leads to intellectual disability. Issue 4 (7th January 2020) - Larcher, Lise; Buratti, Julien; Héron‐Longe, Bénédicte; Benzacken, Brigitte; Pipiras, Eva; Keren, Boris; Delahaye‐Duriez, Andrée
Abstract: The guanine exchange factor subunit eEF1Bα encoded by the EEF1B2 gene belongs to the eukaryotic elongation translational machinery. Pathogen variants in genes of the translational machinery have been associated with several neurodevelopmental disorders. However, only one family of three siblings with intellectual disability (ID) has been reported so far with a homozygous variant in EEF1B2. Here, we report a second family with a novel homozygous loss of function (LoF) variant p.(Ser128*), carried by two siblings with moderate ID and seizures. Our findings confirm the role of EEF1B2 variants in the pathogenesis of autosomal‐recessive ID, expand the variant spectrum and precisely describe the clinical consequences of the LoF of EEF1B2 . Abstract :